students' Multiple Intelligence in Learning during TOEFL Preparation - Rahmalia, indah (Universitas PGRI Sumatera Barat, 2016)
The purpose of this study was to find out students’ Multiple intelligece in learning during TOEFL preparation at STKIP Abdi Pendidikan Payakumbuh. This study was carried out of descriptive research that undertaken through phenomenological approach by employing questionnaire to 31 students selected by using purposive sampling technique. The findings of this study showed that the most multiple intelligence used by the students was musical intelligence with the score 606 , while the multiple intelligences that less dominant used by the students was logical-mathematical intelligence with the score 531.